Aerosolized semifluorinated alkanes as excipients are suitable for inhalative drug delivery: a pilot study - Tsagogiorgas, Charalambos; Jung, Toni; Krebs, Jörg; Yard, Benito A. (International journal of pharmaceutics, 2012)
Semifluorinated alkanes (SFAs) have been described as potential excipients for pulmonary drug delivery, but proof of their efficacy is still lacking. We tested whether SFA formulations with the test drug ibuprofen can be nebulised and evaluated their pharmacokinetics. Physico-chemical properties of five different ibuprofen formulations were evaluated: an aqueous solution (H2O), two different SFAs (perfluorohexyloctane (F6H8), perfluorobutylpentane (F4H5)) with and without ethanol (SFA/EtOH). Nebulisation was performed with a jet catheter system. Inhalative characteristics were evaluated by laser diffraction. A confirmative animal study with an inhalative single-dose (6mg/kg) of ibuprofen with each formulation was performed in anaesthetised healthy rabbits. Plasma samples at defined time points and lung tissue harvested after the 6-h study period were analyzed by HPLC-MS/MS. Pharmacokinetics were calculated using a non-compartment model. All formulations were nebulisable. No differences in aerodynamic diameters (MMAD) were detected between SFA and SFA/EtOH. The ibuprofen plasma concentration-time curve (AUC) was highest with F4H5/EtOH. In contrast, F6H8/EtOH had the highest deposition of ibuprofen into lung tissue but the lowest AUC. All tested SFA and SFA/EtOH formulations are suitable for inhalation. F4H5/EtOH formulations might be used for rapid systemic availability of drugs. F6H8/EtOH showed intrapulmonary deposition of the test drug.